Medicinal plants from the East - Wiart, Christophe (Nottingham, [England] Nottingham University Press, 2009)
"Many of the plants included in this book have not yet been studied and readers may use it as a reference material to start new research projects or to start international research collaborative programs. The book names, classifies, identifies and even locates some plants which, for most the most part, have not been studied for pharmacology. The geographical areas covered include East Africa, India, Sri Lanka, Bangladesh, Nepal, Burma, Laos, Vietnam, Cambodia, Thailand, Korea, Malaysia, Indonesia, China, Japan, Taiwan, the Philippines, Papua New Guinea, Australia, the Pacific Islands, Hawaii and the US. Clear, precise, botanical plates for each plant are used, most of which are illustrated for the first time and perhaps the last. Details on flowers, fruits, leaves, even anthers are given. Each plate provides all possible details, including origin of the herbarium, location of the plant, name of the plant collector and date of collection, plus some field notes including ecological data. None of the plates has been published before. A very precise botanical description, based both on fresh samples and herbaria, is also given, helping the reader to identify their plants or to use them as a reference material. Plants are introduced according to their subclass, family, and order, with reference to the general pharmacological and chemical profiles in these botanical groups. This allows the reader to understand and even predict the pharmaceutical potentials of the plant mentioned. This type of presentation gives a logical overview demonstrating that pharmacological properties depend on botanical classification. The scientific names are provided for each plant, with complete synonym, occasionally basionym, and vernacular names (English and numerous local languages), providing the reader with a strong, reliable and accurate set of data to identify the plant. The etymology of the scientific name of each plant is also provided."--Publisher's description.
Includes bibliographical references and index.
Keywords: Medicinal plants -- Asia